Answer:
[tex]x = \frac{-5+/-\sqrt{57} }{2}[/tex]
Step-by-step explanation:
To solve the quadratic equation, rearrange it into [tex]ax^2+bx+c[/tex].
[tex]x^2=-5x+8\\x^2 + 5x-8[/tex]
This quadratic is not factorable and to solve needs the quadratic formula.
The quadratic formula is [tex]x=\frac{-b+/-\sqrt{b^2-4ac} }{2a}[/tex]. Here a=1, b=5, and c=-8.
Substitute and you'll have:
[tex]x=\frac{-b+/-\sqrt{b^2-4ac} }{2a} =\frac{-5+/-\sqrt{5^2-4(1)(-8)} }{2(1)}=\frac{-5+/-\sqrt{25+32} }{2)}[/tex]
[tex]\frac{-5+/-\sqrt{57} }{2}[/tex]